2011
DOI: 10.1590/s1807-59322011000500029
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-β in graft vessels: histology and immunohistochemistry

Abstract: OBJECTIVES:The biological functions of transforming growth factor-β signaling that involves Smad proteins have not been previously investigated with respect to coronary artery bypass grafts. The aim of the present study was to observe the immunostaining of proteins that are related to this signaling pathway.METHODS:Fifteen remnants of coronary artery bypass grafts, including nine saphenous veins, three radial arteries and three mammary arteries, were collected from 12 patients who were undergoing coronary arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
0
7
0
1
Order By: Relevance
“…Graft failure is common following coronary artery bypass grafting [ 40 , 41 ] puzzling vascular biologists and surgeons as to mechanisms. Yuan et al [ 42 ] have shown that severe vascular wall degeneration and collagen deposition together with overexpressed TGF- β signaling cytokines were responsible for failure (early and late) of the saphenous vein and radial artery grafts. As TGF- β is responsible for NH in a number of vascular disease models that have similarities to the arterialized vein in an AVF, targets to impede this early gene signaling may be future directions to help retard the aggressive NH which occurs in AVF.…”
Section: Cytokines/inflammationmentioning
confidence: 99%
“…Graft failure is common following coronary artery bypass grafting [ 40 , 41 ] puzzling vascular biologists and surgeons as to mechanisms. Yuan et al [ 42 ] have shown that severe vascular wall degeneration and collagen deposition together with overexpressed TGF- β signaling cytokines were responsible for failure (early and late) of the saphenous vein and radial artery grafts. As TGF- β is responsible for NH in a number of vascular disease models that have similarities to the arterialized vein in an AVF, targets to impede this early gene signaling may be future directions to help retard the aggressive NH which occurs in AVF.…”
Section: Cytokines/inflammationmentioning
confidence: 99%
“…TGFβ family includes a structurally diverse set of more than 33 cytokines that regulate the differentiation, proliferation, migration and survival of diverse cell types [46]. As Shi-Min Yuan et al (2011) states that severe vascular wall degeneration and collagen deposition together with overexpressed TGF-β signalling cytokines may provide preliminary evidence for the failure of the saphenous vein grafts [47]. This might indicate internal thoracic artery grafts longer durability.…”
Section: Discussionmentioning
confidence: 99%
“…Aortic tissue samples were fixed in 10% methanol solution in 1 mm 3 blocks, embedded in paraffin wax, processed routinely, and stained with hematoxylin and eosin on 4-µm sections ( 9 ). Immunohistochemical staining of α-SMA was performed using EnVision method ( 9 ). A primary antibody α-SMA sc-58671 (1:100) purchased from Santa Cruz Biotechnology, Inc., CA, USA, was used.…”
Section: Methodsmentioning
confidence: 99%